2008
DOI: 10.1007/s00192-008-0569-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of autologous fascial slingplasty procedure for treating female urinary incontinence

Abstract: The aims of this study were to compare the pre- and postoperative urodynamic findings of the suburethral autologous rectus fascial sling procedure and to determine patient satisfaction with the procedure by telephone interviews. Eight-four female patients with urodynamic stress incontinence completed a multi-channel urodynamic study and pad test before and after the operation. Subjective and objective satisfaction were also recorded. Significant changes were noted in the stress maximal urethral closure pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This value is consistent with the literature ones, 83% to 94% 8,[14][15][16] . Table 2 -Table 2 -Table 2 -Table 2 -Table 2 Table 3 -Table 3 -Table 3 -Table 3 - Table 3 Analysis of variance with summary measures (General).…”
Section: Results Results Results Resultssupporting
confidence: 94%
“…This value is consistent with the literature ones, 83% to 94% 8,[14][15][16] . Table 2 -Table 2 -Table 2 -Table 2 -Table 2 Table 3 -Table 3 -Table 3 -Table 3 - Table 3 Analysis of variance with summary measures (General).…”
Section: Results Results Results Resultssupporting
confidence: 94%
“…34 In another aspect, the pathophysiology of postoperative de novo OAB after MUS remains not fully understood. Previous studies 33 indicated several factors which might contribute to the development of de novo OAB symptoms, such as nerve damage to the bladder during dissection, 35 bladder outlet obstruction, 36 or reaction to the foreign body. 37 The combination of LSC and MUS may increase the risk for the postoperative de novo OAB incidence from different etiologies.…”
Section: Resultsmentioning
confidence: 99%